Portopulmonary Hypertension: A Survey of Practice Patterns and Provider Attitudes. Issue 6 (June 2019) - DuBrock, Hilary M.; Salgia, Reena J.; Sussman, Norman L.; Bartolome, Sonja D.; Kadry, Zakiyah; Mulligan, David C.; Jenkins, Sarah; Lackore, Kandace; Channick, Richard N.; Kawut, Steven M.; Krowka, Michael J.
Abstract : Background: The role of liver transplantation (LT) in the management of portopulmonary hypertension (POPH) is poorly understood. The aim of this study was to better understand provider attitudes and practice patterns regarding the management of patients with POPH and to assess the concordance between clinical practice and current guidelines. Methods: We performed a multicenter survey study of hepatologists and pulmonary hypertension (PH) physicians at US LT centers that performed >50 transplants per year. Survey responses are summarized as number (%). Associations were assessed using a Wilcoxon-rank sum, chi-square, or Fisher exact test, as appropriate. Results: Seventy-four providers from 35 centers were included. There was marked variability regarding screening practices, management, and attitudes. Forty-two percent responded that POPH nearly always or often improves with LT, and 15.5% reported that POPH rarely or never improves. In contrast to current guidelines, 50.7% agreed that treated POPH should be an indication for LT in patients with compensated cirrhosis. Hepatologists were more likely than PH physicians to agree that POPH should be an indication for LT ( P = 0.02). Forty-nine percent of respondents thought that the current POPH Model for End-stage Liver Disease exception criteria should be modified, and management of patients with an elevated mean pulmonary arterial pressure and normal pulmonary vascular resistance differed from current policies. Conclusions: There is marked variability in provider attitudes and practice patterns regarding the management of POPH. This study highlights the need for prospective studies to inform practice and for improved implementation of practice guidelines in order to standardize care. Abstract : Supplemental Digital Content is available in the text.